Comparative Safety, Immunogenicity, and Efficacy of CEF Cell-Based and DF-1 Cell Line Adapted Infectious Bursal Disease Vaccines in Specific-Pathogen-Free Chickens - Daniel Workineh; Molalegne Bitew; Daniel Oluwayelu; Belayneh Getachew; Takele Abayneh; Esayas Gelaye; Hawa Mohammed; Tedros Fikru; Mastewal Birhan; Bereket Dessalegn; Getaw Deresse; Kassaye Adamu; et al. (Journal of Immunology Research, 2022)
Infectious bursal disease (IBD) is an immunosuppressive and economically important disease of young chickens caused by infectious bursal disease virus (IBDV). The National Veterinary Institute (Bishoftu, Ethiopia) produces intermediate IBDV vaccine using primary chicken embryo fibroblast (CEF) cells, a method with technical and economical cumbersome. This study assessed the safety, immunogenicity, and efficacy of DF-1 cell line-adapted IBDV LC–75 vaccine strain in reference to the CEF-based vaccine. Confluent monolayer of DF-1 cells was infected with IBDV and cells with cytopathic effects were passaged until 3rd passage. Viral growth was confirmed using a one-step RT-PCR targeting IBDV VP2 gene. Viral titer increased from 1st passage through 3rd passage. Safety was assessed in 30 specific-pathogen-free chickens (15 chickens/group) injected with 10-fold field dose of each vaccine intraocularly and monitored for 21 days. For immunogenicity and efficacy, 60 specific-pathogen-free chickens were grouped into 3 (20 chickens/group). First and 2nd group received DF-1 cell and CEF-based IBDV vaccines, respectively. The 3rd group served as unvaccinated control. Antibody response was measured using iELISA. Chickens were challenged 4 weeks postvaccination with very virulent IBDV (vvIBDV) intraocularly and followed-up for 10 days. Vaccination did not cause any adverse reactions during the 21 days of follow-up. In addition, both vaccines induced higher antibody titer 14 and 24 days-post-vaccination as compared to unvaccinated controls (p<0.05). Moreover, DF-1 and CEF-based IBDV LC–75 vaccines rendered a complete protection against vvIBDV. Contrarily, morbidity and mortality in unvaccinated chickens was 50% and 30%, respectively. The results indicated that DF-1 and CEF cell-based IBDV vaccines are comparably immunogenic and efficacious. Therefore, DF-1 cell-line can be considered an affordable and convenient alternative to the CEF-based approach. The suitability of DF-1 cells to grow other IBDV strains and safety of these vaccines on bursa of Fabricius should further be investigated.